2006
DOI: 10.1038/sj.onc.1209384
|View full text |Cite
|
Sign up to set email alerts
|

Chronic UVA irradiation of human HaCaT keratinocytes induces malignant transformation associated with acquired apoptotic resistance

Abstract: Ultraviolet A (UVA, 315-400 nm), constituting about 95% of ultraviolet irradiation in natural sunlight, represents a major environmental challenge to the skin and is clearly associated with human skin cancer. It has proven difficult to show direct actions of UVA as a carcinogen in human cells. Here, we demonstrate that chronic UVA exposures at environmentally relevant doses in vitro can induce malignant transformation of human keratinocytes associated with acquired apoptotic resistance. As evidence of carcinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(86 citation statements)
references
References 36 publications
(42 reference statements)
3
82
1
Order By: Relevance
“…Furthermore, treatment with UV radiation may induce intracellular mutations, which may in turn induce malignant transformation. The results of previous studies have suggested that environmentally relevant doses of UVA (>20 J/cm 2 ) irradiation may induce highly pernicious transformation, including anchorage-independent growth, the hypersecretion or overexpression of carcinogenic factors, and alterations in the morphology and apoptosis of keratinocytes (33,34). However, in the present study, clinical doses of UVA irradiation negative influences in HaCaT cells; they promoted the expression of Nrf2 and cellular antioxidant levels.…”
Section: Discussioncontrasting
confidence: 50%
“…Furthermore, treatment with UV radiation may induce intracellular mutations, which may in turn induce malignant transformation. The results of previous studies have suggested that environmentally relevant doses of UVA (>20 J/cm 2 ) irradiation may induce highly pernicious transformation, including anchorage-independent growth, the hypersecretion or overexpression of carcinogenic factors, and alterations in the morphology and apoptosis of keratinocytes (33,34). However, in the present study, clinical doses of UVA irradiation negative influences in HaCaT cells; they promoted the expression of Nrf2 and cellular antioxidant levels.…”
Section: Discussioncontrasting
confidence: 50%
“…Albino hairless mice exposed to UVA irradiation (330 nm) developed tumors after >400 days and even long-wave UVA irradiation (>340 nm) has been found to induce skin carcinomas (for review see de Gruijl, 2002). Furthermore, the immortal human HaCaT keratinocytes became tumorigenic when irradiated with 24 J/cm 2 UVA for 18 weeks (He et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the results of recent studies have shown that the UVA can also be a potent inductor of DNA damage and may be associated with skin cancer 9 . Protracted exposure to UVA leads to lysosomal dysfunction in human fibroblasts 10 , malignant transformation in human cultured keratinocytes 11 and the formation of skin carcinomas in hairless mice in vivo 12 . Unlike the shorter-wavelength UVB photons, which are almost completely absorbed by the epidermis, the longerwave length UVA photons can reach deeper dermal layer of skin and its blood vessels.…”
Section: Introductionmentioning
confidence: 99%